MANAJEMEN PEMBELAJARAN PADA PELAJARAN PRODUKTIF LISTRIK DI SMK MELALUI GABUNGAN METODE CERAMAH DENGAN METODE KOOPERATIF MODEL TPS (THINK PAIR SHARE) - Zulhamdi Zulhamdi Zulhamdi (Manajer Pendididikan, 2016)
To be able to learn something well, students need to hear, see, ask questions about it, and discuss it with others. Not only that, students need to describe in their own way, shows anexample, practicing and writing tasks. This study uses action research (action research) three cycles . Each cycle consists of four phases: design, activities and observations, reflections, and revisi . Data obtained in the form of the results of formative tests and observation sheet. From the analyst found that student achievement has increased from the first cycle to the third cycle, namely, the first cycle (73.33 %), the second cycle (80.00 %), the third cycle (93.33 %). The conclusions of this study is a cooperative model of TPS (Think Pair Share) can be a positive influence on students' motivation in learning electric productive.Keywords: learning electric productive, think par share